Karakteristik Guru Profesional dalam Meningkatkan Kualitas Pembelajaran di Pendidikan Dasar - Afriani Azzahra; Sakilah Sakilah; Anisa Anisa; Nabila Zaskia; Hani Kurnia; Zumi Nur Faiza (PT. Global Pustaka Ilmiah, 2026)
Teaching is a profession that requires specialized expertise and authority in education, instruction, and training, and therefore cannot be performed by individuals without the necessary professional qualifications. According to Law of the Republic of Indonesia No. 14 of 2005 concerning Teachers and Lecturers, professional educators are required to possess four core competencies: pedagogical, personal, social, and professional competencies. This article aims to examine the nature of teacher professionalism, analyze the strategic role of teachers in the instructional process, and explore the importance of discipline, responsibility, and moral integrity in upholding the professional code of ethics, particularly within the context of primary education. This study employs a theoretical review method by drawing upon relevant scholarly literature and previous research findings. The review concludes that the four teacher competencies are interdependent and cannot be separated. A balanced integration of instructional competencies (pedagogical and professional) with personal qualities (personal and social competencies) constitutes the fundamental basis for fostering high-quality learning processes and enhancing the overall quality of national education in Indonesia.